Congenital Portosystemic Shunts and Liver Hemangiomas in Children: Is There an Association?. Issue 6 (August 2021) - Kumar, Manjusha; Natarajan, Kannan; Dunn, Rachel; Khan-Serrano, Aliyah; Nakar, Charles; Rampersad, Angeli; Kumar, Anil
Abstract : Liver hemangiomas are benign vascular tumors of infancy. They can have vascular shunting mostly arteriovenous and sometimes arterioportal or portosystemic, which improves as hemangiomas involute. In contrast, congenital portosystemic shunts are developmental vascular anomalies that may go undetected for years, with significant sequelae. We describe a child with a history of multiple cutaneous and liver hemangiomas in infancy and later diagnosis of congenital portosystemic shunt. Past experience of a similar patient and a current baby followed for liver hemangiomas with portosystemic shunts, is also shared. Literature is reviewed for known association. We suggest longer-term follow-up for babies with liver hemangiomas. Abstract : Supplemental Digital Content is available in the text.